Effects of non-toxic filamentous cyanobacteria isolated from tri an reservoir on Daphnia - Luu, Pham Thanh; Yen, Tran Thi Hoang; Thai, Tran Thanh; Quang, Ngo Xuan (Academia Journal of Biology, 2020)
This study is aimed to examine whether the presence of non-toxic ﬁlamentous cyanobacteria can cause toxic effects on Daphnia magna. Six strains of Oscillatoria perornata were isolated from the Tri An Reservoir and cultured in our laboratory for investigation. The results revealed that all strains were negative with the mcyA moleculer marker. The high performance liquid chromatography (HPLC) results showed that toxin was not detected in their culture products, indicating that these strains corresponded to non-toxin producing strains. However, the results of chronic assay indicated that these non-toxin producing O. perornata conferred toxic effects on the tested animals. The age at first reproduction of D. magna was delayed and the survival of D. manga decreased in proportional with the increase of the density of cells of O. perornata exposed. Significant differences in the life history responses were observed for D. mangna exposed to O. perornata. These results suggested that bioactive secondary metabolites other than microcystins produced by the filamentous cyanobacteria O. perornata may contribute to the toxic effects on Daphnia. Besides cyanotoxins, other secondary metabolites must be taken into account when investigating the toxic effects of cyanobacteria.